Hubungan Sense of School Belonging dengan Well-Being pada Siswa SMA - Marsyanda, Marsyanda; Hastuti, Rahma (Fakultas Tarbiyah IAI Nasional Laa Roiba, 2024)
This study aims to explore the relationship between students' engagement in school and their mental well-being. Data were collected from 183 high school students through the convenience sampling method. Spearman's correlation analysis and One-Sample Kolmogorov-Smirnov test we’re used to analyze the data. The results showed that there was a significant positive relationship between students' engagement in school and their mental well-being. These findings suggest that students who feel more involved in school have higher levels of mental well-being. This research provides a clear understanding of the importance of student engagement and their well-being in achieving higher academic and non-academic achievements. The practical implication of this research is the importance of increasing student involvement in schools to create a conducive learning environment and improve overall student welfare. Future research can explore the relationship between student involvement in school and other factors such as student self-esteem and self-efficacy